The Role of Services in Rural Income : The Case of Vietnam - Aksoy, M. Ataman; Isik-Dikmelik, Aylin (World Bank, Washington, DC, 2012)
This paper investigates the role of services in the household response to trade reforms in Vietnam. The relative response of the households and income growth after a major trade liberalization in rice are analyzed aiming to answer the following questions: What type of households, in which locations, having access to what type of services, benefited more from the reforms? It focuses on services that have an impact on transaction costs (roads or quality of roads, public transportation, access to credit, extension services, and availability of markets in communication services) because transaction costs are often cited as a barrier to rural households in responding to the price changes and increased incentives offered by trade and other policy reforms. The results suggest that availability of production related services contributes positively to the impact of trade reforms. Although most of the service variables have a positive and significant effect on growth in income, some that are expected to have an impact are not significant. This may be explained by the exceptional coverage of infrastructure services in Vietnam even before the reforms. When service availability is very similar across different localities, household characteristics become more important in determining the response.